(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Nowadays simulation is becoming a common tool for various processes analysis, whether it is a video game, local weather forecast, or any other area of daily life. FlexSim software provides virtual environment with the ability to simulate any process with as much information as the user needs. FlexSim simulations are commonly applied in areas such as manufacturing, warehousing, distribution of goods and products, materials processing etc. The aim of this presentation is to show how FlexSim software can be integrated into textile orientated study programs and to illustrate its application possibilities in the analysis of garment production process. Also, to take measures to increase the efficiency of production flow by eliminating its bottlenecks.